The relationship between mesoscale eddies and the abundance and distribution of jumbo flying squid off Chile - Wu, Xiaoci; Jin, Pengchao; Yu, Wei (Frontiers in Marine Science, 2025)
Jumbo flying squid (Dosidicus gigas), an essential commercial fisheries species in the Humboldt Current System (HCS), is highly sensitive to changes in the marine environment. Mesoscale eddies are prevalent oceanographic phenomena that play a pivotal role in circulation, material transport, and ecosystem dynamics within the ocean. The waters off Chile in the south-central part of the HCS serve as one of the primary fishing grounds for D. gigas. This region is characterized by active mesoscale eddies that regulate biogeochemical processes. However, the impacts of mesoscale eddies on D. gigas off Chile remain unclear. To address this knowledge gap, this study analyzed the spatiotemporal distribution of mesoscale eddies in this region using a global mesoscale eddy dataset. By integrating environmental and D. gigas fishing data, we assessed the influence of these mesoscale eddies, and their associated environmental changes, on the abundance and distribution of D. gigas. Results revealed that mesoscale eddies were mainly formed in the coastal areas of Chile, with monthly and annual variations in their occurrences. A positive correlation was observed between the number of eddies and the abundance of D. gigas. Cyclonic eddies (CEs) were found to harbor a higher aggregation of D. gigas compared to anticyclonic eddies (AEs). An analysis of the proportion of key environmental factors within suitable ranges for the two types of eddies indicated that the number and proportion of key environmental factors—particularly sea surface temperature (SST)—within suitable ranges were higher in CEs. This study concludes that CEs provide more suitable environmental conditions than AEs, thereby supporting the aggregation of D. gigas.